The little yellow leaf - Berger, Carin (New York : Greenwillow Books, 2008)
A yellow leaf is not ready to fall from the tree when autumn comes, but finally, after finding another leaf still on the tree, the two let go together.
Kirkus Review.
4.9
K-3
Keywords: Leaves -- Juvenile fiction; Leaves -- Fiction; Autumn -- Fiction; Leaves -- Fiction